Neural reward processing is modulated by approach: and avoidance-related personality traits - Simon, Joe J.; Walther, Stephan; Fiebach, Christian; Friederich, Hans-Christoph; Stippich, Christoph; Weisbrod, Matthias; Kaiser, Stefan (NeuroImage, 2010)
The neural processing of reward can be differentiated into two sub-components with different functions, “wanting” (i.e., the expectation of a reward which includes appetitive and motivational components) and “liking” (i.e., the hedonic impact experienced during the receipt of a reward), involving distinct neural systems. We hypothesize that variability in neural reward processing previously observed in healthy subjects could reflect inter-individual differences in personality. Therefore, the aim of this study was to investigate how the neural processing during expectation and reception of a reward depends on interpersonal differences in reward sensitivity, more specifically the tendency to approach vs. avoid reward-related situations. We employed event-related functional magnetic resonance imaging during a monetary incentive delay task. Subjects with a high approach motivation showed more activation of the Ventral Striatum (VS) during the receipt of a reward, and more medial orbitofrontal activity during both the receipt and omission of a reward. Subjects with a high behavioral inhibition showed less activation in the VS during the receipt of a reward. These findings indicate that the tendency to approach or avoid reward-related situations exhibits a distinct relation with neural reward processing. Specifically, subjects with high behavioral approach appear to be sensitive mainly to positive outcomes and to a lesser extent to the omissions of rewards, whereas subjects with low behavioral approach as well as those with a high inhibition tendency display a blunted response to rewards.
Available online 18 September 2009
Gesehen am 01.08.2023